Prinsip Kehati-Hatian yang Wajib Diterapkan oleh Notaris dalam Pembuatan Akta Kuasa Menjual - Jim Jeffrey Prajogo; Fully Handayani Ridwan (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
In property sale and purchase transactions, there are situations where the owner delegates authority to another party to sell the property without the owner’s presence. In such cases, a supporting document is required to confirm that the asset is entrusted by the owner to the designated party. This document is the Power of Attorney to Sell. Issues arise when there is document forgery or incompleteness, impacting related parties and leading to legal defects. This problem is analyzed using doctrinal research methods, focusing on the caution exercised by notaries in drafting the Power of Attorney to Sell. Such caution is implemented as a measure to ensure legality and prevent potential legal risks in the future. A notary drafts the Power of Attorney to Sell with meticulous care and attention to provide legal protection for the parties involved. Furthermore, this study highlights the consequences of a lack of caution for notaries and the involved parties. The findings indicate that meticulous analysis is crucial for notaries to protect the involved parties and demonstrate their professional performance.